Praktik Monopoli PT Perusahaan Gas Negara Di Area Medan; Studi Putusan Terhadap Putusan Mahkamah Agung Nomor 511 K/Pdt.Sus KPPU/2018 - Nada Halillah; Indra Rahmatullah (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThe Business Competition Supervisory Commission is an independent institution that deals with competition law in Indonesia. Legislation that comprehensively regulates business competition is Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. But many business actors violated Law Number 5 of 1999. One of them was the case of PT Perusahaan Gas Negara, which was suspected of having a monopoly because of an increase in gas prices in the Medan area. This study uses normative legal research methods and literature studies. The conclusion of this research is that PT Perusahaan Gas Negara did not conduct a monopoly, but the company's activities in setting prices in the terrain in August November included objects that were exempted from the provisions of the Law in article 50 letter a of Law Number 5 of 1999.Keywords: Monopoly, Supreme Court.